2
$\begingroup$

How to find the square root of an irrational expression, to simplify that root. e.g.:

$$ \sqrt{ 8 - 4\sqrt{3} } = \sqrt{6} - \sqrt{2} $$

Easy to verify:

\begin{align} (\sqrt{6} - \sqrt{2})^2 = 6 - 2\sqrt{12} +2 = 8 - 4 \sqrt{3} \end{align}

But how to work it out in the first place? I feel there's a standard technique (Completing-the-square? Quadratic formula?), but don't recall it or what it's called...

BTW: this came up in verifying equivalence of different calculations of $\cos{75°}$ (the above divided by $4$), as $\cos{\frac{90°+60°}{2}}$ vs $\cos{(45°+30°)}$, from 3Blue1Brown's lockdown video on complex numbers and trigonometry.

$\endgroup$
  • 2
    $\begingroup$ The term of art (and it really is something of an art) is "denesting radicals". That should help you search for references. $\endgroup$ – Blue May 24 at 5:36
  • $\begingroup$ perhaps you could assume that the inner expression is a perfect square, then reform so that the inner radical has a coefficient of two. e.g. $\sqrt{8-4\sqrt{3}} = \sqrt{8-2\sqrt{12}}=\sqrt{6-2\sqrt{12}+2}=\dots$ $\endgroup$ – John Joy May 24 at 6:12
3
$\begingroup$

I don't think there's a name for this procedure but let's apply it to $\sqrt{8-4\sqrt3}$. If you suspect this equals $\sqrt a\pm\sqrt b$ with rationals $a$ and $b$, then $$8-4\sqrt3=(\sqrt a\pm\sqrt b)^2=(a+b)\pm2\sqrt{ab}$$ so you want to solve simultaneously $a+b=8$ and $-4\sqrt{3}=\pm2\sqrt{ab}$. So you need the minus sign, and $ab=12$. Then $a$ and $b$ are roots of the quadratic equation $$(X-a)(X-b)=X^2-(a+b)X+ab=X^2-8X+12.$$ This does has rational roots: $2$ and $6$.

| cite | improve this answer | |
$\endgroup$
3
$\begingroup$

Note the denesting formula

$$ \sqrt{a-\sqrt c} = \sqrt{\frac{a+\sqrt {a^2-c}}2}- \sqrt{\frac{a-\sqrt {a^2-c}}2} $$

which can be verified by squaring both sides, and apply it to

$$\sqrt{8-4\sqrt3}=2\cdot \sqrt{2-\sqrt3}= 2\left(\sqrt{\frac32} -\sqrt{\frac12}\right)=\sqrt6-\sqrt2 $$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

If I recall correctly, you make the assumption that your expression takes the form $\sqrt{a}\pm\sqrt{b}$:

$\sqrt{8-4\sqrt{3}} = \sqrt{a}\pm\sqrt{b}$

$8-4\sqrt{3} = 8-\sqrt{48} = a\pm2\sqrt{ab}+b$

We can see that the irrational part must be assigned the negative sign.

Equating rational and irrational parts:

$a+b = 8$

$-2\sqrt{ab} = -\sqrt{48} \implies ab = 12$

Then $a = \frac{12}{b} \implies \frac{12}{b}+b = 8 \implies 12 + b^2 = 8b \implies b^2 - 8b + 12 = (b-6)(b-2) = 0$

Since we know the answer is positive, take b = 2 and a = 6.

$\sqrt{8-4\sqrt{3}} = \sqrt{6}-\sqrt{2}$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.